Study of the Fumigation Antimicrobial Activity and Mechanism of Essential Oil - Xuejuan DUAN; Tong ZHANG; Jieying ZENG; Xiaola LI; Guitao CHEN; Zixuan CHENG; Yali HAN; Kegang WU (Shipin gongye ke-ji, 2023)
In this study, the antibacterial effects of six plant essential oils against four common bacteria in the vapor phase was investigated by plate fumigation method with the measurement of the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The combination of essential oils with better bactericidal effect was studied and applied to keep fresh of capsicum frutescens. The antibacterial mechanism of cinnamon essential oil against Escherichia coli (E. coli) was also determined by transmission electron microscopy (TEM) and electric conductivity. The results showed that citronella essential oil, cinnamon essential oil and basil essential oil had more significant antibacterial effect, which could inhibit all tested bacteria at the concentration of 0.125 μL/mL. Citronella essential oil and cinnamon essential oil had better bactericidal effect, which could kill all the tested bacteria except Pseudomonas aeruginosa at the concentration of 0.125 μL/mL. Blended essential oils with the ratio of citronella essential oil, cinnamon essential oil and basil essential oil being 4:1:8, demonstrated the best antibacterial activity. The blended essential oils showed synergistic effects on E. coli and Salmonella, but antagonistic effect on Staphylococcus aureues. GC-MS indicated that the antibacterial ability of citronella essential oil mainly came from citronellal, geraniol and citronellol, cinnamon essential oil came from cinnamaldehyde and basil essential oil came from estragole and linalool. The application of blended essential oil in modified atmosphere preservation of capsicum frutescens had a better preservative and fresh-keeping effects when the spatial concentration of blended essential oil was 0.125 μL/mL. TEM showed morphological changes and cell membrane shrinkage of E. coli after fumigation with cinnamon essential oil. The conductivity test showed that the membrane permeability of E. coli increased after fumigation, which resulted in electrolyte leakage. In conclusion, the possible antibacterial mechanism of vapor-phase cinnamon essential oil against E. coli is to change the cell morphology and membrane permeability.